RESPON PERTUMBUHAN BIBIT INDUK JAMUR TIRAM PUTIH (Pleurotus ostreatus) PADA LIMA MEDIA BIJI SORGUM - Damianus Pati; Rikka W. Sir (Partner, 2010)
Growth Response Of Pleurotus Ostreatus Parent Seed At Five Different Sorghum Medium. The research was conducted in Biotechnology Laboratory of Kupang State Agricultural Polytechnic in one month, December 2008. The research was aimed to know the growth response of Pleurotus ostreatus parent seed at five different sorghum medium.This research used sorghum seed as mycelium of Pleurotus ostreatus growth medium. The variables that used to measure were mycelium growth time and mycelium of Pleurotus ostreatus scattered which measured from the beginning of mycelium scattered. The result shown that the fastest growth and scattered of Pleurotus ostreatus mycelium was Sikun sorghum and the lowest growth and scattered of Pleurotus ostreatus mycelium was Pisan sorghum.Keywords : Sorgum, Parent seed, Growth